STUDI PEMILIHAN LOKASI ALTERNATIF PELABUHAN TRISAKTI BANJARMASIN PROPINSI KALIMANTAN SELATAN - Syaefudin, Syaefudin (Jurnal Hidrosfir Indonesia, 2008)
The operational of Trisakti port , Banjarmasin, South Kalimantan is only 3 hoursperday due to sedimentation and sea lane damaged. This condition became worse inline with forest conversion in hinterland area. Selection of alternative port was carried out at seven coastal areas in Tanah Laut regency. Based on the result of multicriteria analysis, the best location for alternative port is Batakan-Tanjung Coast.